2013
DOI: 10.1007/s10103-012-1261-6
|View full text |Cite
|
Sign up to set email alerts
|

Microtensile bond strength analysis of adhesive systems to Er:YAG and Er,Cr:YSGG laser-treated dentin

Abstract: The aim of this in vitro study was to evaluate the effect of different surface treatments (control, diamond bur, erbium-doped yttrium aluminum garnet (Er:YAG) laser, and erbium, chromium:yttrium-scandium-gallium-garnet (Er,Cr:YSGG) laser) on sound dentin surface morphology and on microtensile bond strength (μTBS). Sixteen dentin fragments were randomly divided into four groups (n = 4), and different surface treatments were analyzed by scanning electron microscopy. Ninety-six third molars were randomly divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
2
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 37 publications
2
32
2
5
Order By: Relevance
“…The water molecules among the hydroxyapatite crystals absorb the beams and evaporate; as a result, the internal pressure increases and microexplosions occur leading to substrate ejection and microstructural alterations. 25,28,29 Although several studies have assessed the effects of erbium family lasers on bleached enamel, 3,[30][31][32] to the best of our knowledge no study has compared the effects of Er:YAG and Er,Cr:YSGG lasers on bleached dentin. Based on our results, Er:YAG laser irradiation led to significantly higher bond strength compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The water molecules among the hydroxyapatite crystals absorb the beams and evaporate; as a result, the internal pressure increases and microexplosions occur leading to substrate ejection and microstructural alterations. 25,28,29 Although several studies have assessed the effects of erbium family lasers on bleached enamel, 3,[30][31][32] to the best of our knowledge no study has compared the effects of Er:YAG and Er,Cr:YSGG lasers on bleached dentin. Based on our results, Er:YAG laser irradiation led to significantly higher bond strength compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have evaluated the immediate bond strengths of current dental adhesive systems to the dental hard tissues irradiated by Er,Cr:YSGG laser, aiming to determine whether Er,Cr:YSGG laser-irradiated dental hard tissues offer a suitable bonding substrate [5][6][7] . Initial studies revealed that irradiation of the dentin using Er,Cr:YSGG laser leads to increase in surface roughness, with open dentinal tubules and no smear layer on the surface, suggesting that the irradiated dentin might provide a favorable substrate for resin bonding 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…3,6,20,21,[26][27][28] Er, Cr; YSGG lazerin sert dokularda, mine ve dentin yüzey-lerinde pürüzlendirmek amacıyla kullanımı pek çok araştırmaya konu olmuştur. [29][30][31][32][33][34] Yine literatüre bakıl-dığında Er:YAG, Nd:YAG, KTP ve CO 2 lazerlerin akrilik rezin yüzeyini pürüzlendirmek amacıyla kullanıldığı birçok araştırma olmasına rağmen, [20][21][22][23][24][25] Er,Cr;YSGG lazerin akrilik rezin tamirinde yüzey işlemi olarak kullanıldığı çalışmanın çok az olduğu görülmektedir. Bu çalışmanın amacı; kumlama ve frezleme gibi mekanik yüzey işlemlerinden sonra değişik enerji seviyelerineki Er,Cr;YSGG lazer uygulamasının otopolimerizan akrille yapılan tamirin transvers dayanıma olan etkisini araştırmaktır.…”
Section: Introductionunclassified